Correlation Between Corneal Biomechanical Indices and the Severity of Keratoconus. Issue 2 (February 2020) - Koh, Shizuka; Inoue, Ryota; Ambrósio, Renato; Maeda, Naoyuki; Miki, Atsuya; Nishida, Kohji
Abstract : Purpose: To investigate the correlations between the biomechanical indices determined in Scheimpflug-based corneal biomechanical assessments and the severity of keratoconus (KC) based on corneal tomographic assessments in patients with different stages of KC. Methods: Fifty-three patients who presented with clinical KC in 1 eye and KC suspect in the fellow eye were included. Corneal tomographic and biomechanical assessments were performed using the Pentacam HR and Corvis ST (Oculus Optikgeräte GmbH, Wetzlar, Germany). Correlations between the tomographic indices and biomechanical indices were assessed, including the anterior radius of curvature (ARC) and posterior radius of curvature (PRC) at a 3.0-mm optical zone and the thinnest pachymetry (Tmin), deformation amplitude ratio max 2 mm (DAR2mm), integrated radius, stiffness parameter at the first applanation, and linear Corvis Biomechanical Index (beta). Results: DAR2mm correlated negatively with ARC (R = −0.722), PRC (R = −0.677), and Tmin (R= −0.650) ( P < 0.001 for all). Integrated radius correlated negatively with ARC (R = −0.700), PRC (R = −0.668), and Tmin (R= −0.648) ( P < 0.001 for all). Stiffness parameter at the first applanation correlated positively with ARC (R = 0.622), PRC (R = 0.601), and Tmin (R = 0.703) ( P < 0.001 for all). The Corvis Biomechanical Index beta correlated negatively with ARC (R = −0.754), PRC (R = −0.755), and Tmin (R= −0.765) ( P < 0.001 for all). Conclusions: Corneal biomechanical indices correlated with corneal tomographic parameters in patients with KC. These findings support the possibility of developing biomechanical-based staging classification for KC in combination with topographic or tomographic indices.